Societal Loss in R2: The Welfare Effects of the Majority Decision Rule in the Spatial Voting Model - Bouwer, Charles (Université d'Ottawa | University of Ottawa, 2018)
The Euclidean distance metric is applied to two dimensions to determine the loss to society of different majority voting rules. The social objective function is the policy which minimizes the distance from voters' preference points. The sample is small due to computational feasibility. The resuIts of this spatial voting model indicate that an average loss of 4% is reasonable and decreases when the data is highly polarized.